High levels of butyrate and propionate in early life are associated with protection against atopy. Issue 4 (25th November 2018) - Roduit, Caroline; Frei, Remo; Ferstl, Ruth; Loeliger, Susanne; Westermann, Patrick; Rhyner, Claudio; Schiavi, Elisa; Barcik, Weronika; Rodriguez‐Perez, Noelia; Wawrzyniak, Marcin; Chassard, Christophe; Lacroix, Christophe; et al.
Abstract: Background: Dietary changes are suggested to play a role in the increasing prevalence of allergic diseases and asthma. Short‐chain fatty acids (SCFAs) are metabolites present in certain foods and are produced by microbes in the gut following fermentation of fibers. SCFAs have been shown to have anti‐inflammatory properties in animal models. Our objective was to investigate the potential role of SCFAs in the prevention of allergy and asthma. Methods: We analyzed SCFA levels by high‐performance liquid chromatography (HPLC) in fecal samples from 301 one‐year‐old children from a birth cohort and examined their association with early life exposures, especially diet, and allergy and asthma later in life. Data on exposures and allergic diseases were collected by questionnaires. In addition, we treated mice with SCFAs to examine their effect on allergic airway inflammation. Results: Significant associations between the levels of SCFAs and the infant's diet were identified. Children with the highest levels of butyrate and propionate (≥95th percentile) in feces at the age of one year had significantly less atopic sensitization and were less likely to have asthma between 3 and 6 years. Children with the highest levels of butyrate were also less likely to have a reported diagnosis of food allergy or allergic rhinitis. Oral administration of SCFAs to mice significantly reduced the severity of allergic airway inflammation. Conclusion: Our results suggest that strategies to increase SCFA levels could be a new dietary preventive option for allergic diseases in children. Abstract : Children with high levels of butyrate or propionate in feces at one year of age have significantly less atopic sensitization compared to children with lower levels. The infant's diet might influence the levels of SCFAs. Oral application of short‐chain fatty acids might protect children against the development of atopic sensitization and airway inflammation.